Estimación de carbono almacenado en biomasa aérea en plantación de Teca (Tectona grandis L.F:), ubicada en la parroquia Huámbi, provincia de Morona Santiago - Villavicencio Gómez, Xavier Alfredo (2015)
This study was the estimation of carbon stored in aboveground biomass of a teak plantation (Tectona grandis L.F), except (roots, necromass and herbaceous vegetation), located in the southern region of the Ecuadorian Amazon. To do permanent sample units of 500 m2 same stands corresponded to 4 according to the ages of the trees were installed, the parameters evaluated were; total height HT, HC commercial height, diameter at breast height DBH, basal determination of forest area and volumen, just as biomass and carbon stored above ground is estimated by determining its binding capacity. The amount of accumulated carbon presented a range of 11,38tonC/ha to 25,35 tonC/ha, displaying an average of 16,17 tonC/ha and a total of 320,18 tons of carbon per plantation area within a 18,67 has, existing statistical differences between stands. The results presented by the plantation were: at age 6 with 11,38tonC/ha, year 8 14,74 tonC/ha, the year 10 with 12,80 tonC/ha, the year 12 25,35 tonC/ha, teak determined that significant amounts of carbon stored per unit area, so it is advisable for afforestation and reforestation in our environment, ecosystem and environmental services offering, contributing to climate change mitigation